An Algorithmic Animation Platform for the Web - Esponda, Margarita (International Journal of Emerging Technologies in Learning (iJET), 2008)
This paper describes a system for generating animations of algorithms for use in the classroom. The animations emulate the individual steps of an algorithm in graphical form and can be posted to the Web. The system is based in Flash. In order to generate an animation the code of an algorithm is extended with annotations which generate the script code. We call our scripting language â??Flashdance